(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Watch was considered as a symbol of status. Earlier watches were used to only tracking the time but today customer’s wants more than that. Wearing the watch represents meticulousness, elegance and convenience attributes. Now the as technology changes year by year, the watch landscape transformed itself immensely over the years. Brands are adopting advent of innovative and deciphering technology to cater different segments of Indian customers. Smart watches becomes a fad amongst the consumers specially youngsters. So these brands while offering to this younger segment, their aim is to offer a product which is technologically complete and advanced feature product.According to the research report of Ken Research India , 25 of the wrist watches industry wears Premium brandsproducts, where as 37-38 of the consumers demand is mid-price segment of the wrist watch. This may observed because of rise in urban population and rise in buying parity. This study emphasis on buying behaviour of youngsters especially college going students and others with age range of 20 to 30 towards wrist watch buying decisions. Total 90 Samples were taken in to consideration. Judgmental sampling technique used in the study. Structured questionnaire was the instrument to collect primary data. SPPS used to analyze collected data. Study observed that